MONPERA LEARNING MEDIA DESIGN TO IMPROVE STUDENT LEARNING OUTCOMES IN LEARNING IPS IN CLASS IV SDN 13 KABILA BONE BOLANGO DISTRICT - Haris Mahmud, Mohamad Dodi Hasan, Isnanto, (International Journal of Innovations in Engineering Research and Technology, 2022)
Formula problem in research this is , How to Design Learning Media Monpera to results studying Social Studies in Class IV SDN 13 Kabila, Bone Bolango District, Research this aim for knowing application media use against results study students in class IV SDN 13 Kabila, Bone Bolango Regency. Population in study this whole students of SDN 13 Kabila, Bone Bolango Regency, sample that is whole student class IV SDN 13 Kabila, Bone Bolango Regency, the results of research and discussion on media validation by media experts were obtained score by 94% with criteria of 'Very Eligible', Material Expert obtained score by 95% with 'Very Eligible 'criteria , and Linguist obtained score of 87.14% with 'Very Eligible' criteria , with score results end from third expert who has validated obtained score of 92.04% with criteria of 'Very Eligible ' whereas in its application use of learning media Monpera obtained score Pretest of 67.33% meanwhile Posttest obtained by 80.26%, so with exists use of learning media Monpera the could increase results study students on load social studies lesson in Class IV SDN 13 Kabila, Bone Bolango District .